2019
DOI: 10.1101/867564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferroptotic pores induce Ca2+ fluxes and ESCRT-III activation to modulate cell death kinetics

Abstract: Ferroptosis is an iron-dependent form of regulated necrosis associated with lipid peroxidation. Despite its key role in the inflammatory outcome of ferroptosis, little is known about the molecular events leading to the disruption of the plasma membrane during this type of cell death. Here we show that a sustained increase in cytosolic Ca 2+ is a hallmark of ferroptosis that precedes complete bursting of the cell. We report that plasma membrane damage leading to ferroptosis is associated with membrane nanopores… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…1 B). The catalytic role of iron in ferroptosis has been highlighted [ 30 , 31 ]. By staining cells with FerroOrange (to detect ferrous ions), we found that NaIO 3 and Erastin-treated cells accumulated excessive ferrous ions, which were significantly blocked by pre-incubation with Fer-1 or DFO, as revealed by the decreased orange fluorescence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 B). The catalytic role of iron in ferroptosis has been highlighted [ 30 , 31 ]. By staining cells with FerroOrange (to detect ferrous ions), we found that NaIO 3 and Erastin-treated cells accumulated excessive ferrous ions, which were significantly blocked by pre-incubation with Fer-1 or DFO, as revealed by the decreased orange fluorescence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that MLKL forms small and selective pores or channels that mediate the movement of ion fluxes but not big molecules in necroptosis [47,49]. In ferroptosis, the exact mechanism of membrane permeabilization is less clear but also seems to involve pore formation in the plasma membrane [67]. Therefore, pore formation has emerged as a common feature underlying different types of regulated necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pore formation has emerged as a common feature underlying different types of regulated necrosis. As an opposing mechanism, membrane repair by the ESCRT machinery counterbalances all these types of cell death by removing the damage sections of the plasma membrane [20,22,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it supports the hypothesis of pores due to lipid oxidation. Also in a manuscript of Lohans Pedrera et al, it was reported that, nanoscale pores are formed prior to lipid oxidation and cause Ca2+ influx into the cell [102].…”
Section: Lipid Oxidation and Pore Formation Beyond Electroporationmentioning
confidence: 99%